Communication strategies for the inclusion of mobile banking in the San Pedro de Cusco market in Peru - Garcia-Alvarez, Brenda (2024)
The purpose of this study is to analyze the perception of communication strategies for the inclusion of mobile banking among women traders in the San Pedro market, located in the province of Cusco, Peru. For this reason, the Yape mobile application of Banco Crédito del Perú (BCP) was chosen, which has resulted in the affiliation of more than 10 million people and the inclusion of 2.2 million people in the financial system. For this study, an interpretive paradigm, qualitative approach with ethnographic design was applied. Twenty semi-structured interviews were conducted with women workers of Mercado San Pedro about Yape’s communication strategies. The research findings indicate that the most effective financial inclusion is direct marketing that communicates about the financial system to an audience that does not constantly consume digital and traditional media.